METABOLITES AND SEMEN CHARACTERISTICS IN DIFFERENT BULLS FERTILITY - F. G. AL-Gebouri; S. M. Eidan (Iraqi journal of agricultural science, 2024)
This study was investigated the relationship between Holstein bulls' fertility with some biomarkers (amino، fatty، and organic acids) and semen characteristics. The study included exploring the relationship among the fertility of Holstein bulls، several biomarkers، and semen characteristics in straws (20-25 straws/bull) preserved for three years. The cows were artificially inseminated (9-10 cows/bull) from semen. Based on the fertility rate، the bulls were divided into three groups، the first bulls of medium fertility (˂65%)، the second of good fertility (65-79%)، and the third of high fertility (>80%). The semen characteristics were evaluated، and the concentration of some amino acids and organic fatty acids was measured in the seminal plasma of bulls using gas chromatography and HPLC. The results revealed significant differences in the fertility rate among the different groups of bulls in favor of the highly fertile bulls. The results did not show any differences in most of the characteristics of the semen، except for a significant increase in the percentage of live sperm in good bulls compared to highly fertile ones. There were no significant differences for all the concentrations of carboxylic and most amino and fatty acids concentrations، except for an increase in the concentration of glycine acid (P˂0.05) and a decrease in the concentration of omega 9 (P˂0.05) in the highly fertile bulls compared to the medium fertile ones. In conclusion، glycine and omega-9 in the seminal plasma of bulls can be regarded as biomarkers of their fertility and the level of carboxylic acids (volatile fatty acids) can be adopted as an indicator of semen quality or energy level in the diet